2015
DOI: 10.1177/0009922815591959
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Social Determinants of Health and Legal Needs for Children With Special Health Care Needs

Abstract: Children with special health care needs (CSHCN) require comprehensive care with high levels of community and government assistance. Medical-legal partnerships may be particularly suited to address needs for this population. To explore this, we conducted in-depth telephone interviews of families of CSHCN cared for in the primary care practice of our tertiary care children's hospital. The majority of the sample (N = 46) had been late on housing payments and 17% of homeowners had been threatened with foreclosure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…Due to these issues of using geographic measures to predict transplant outcomes, alternative strategies must be considered for evaluating socioeconomic disparities in transplantation. The implementation of systematic screening for social determinants of health (SDH) has been previously described in primary care settings [29, 30], and could be added to reporting requirements for transplant candidate registration. While such screening could provide accurate patient-level SES data, standardized collection of SDH in clinical settings entails its own challenges, including a lack of consensus on best measurements and data collection practices, lack of collaboration between health systems and social services organizations, and technological challenges to capturing and retaining these data [31].…”
Section: Discussionmentioning
confidence: 99%
“…Due to these issues of using geographic measures to predict transplant outcomes, alternative strategies must be considered for evaluating socioeconomic disparities in transplantation. The implementation of systematic screening for social determinants of health (SDH) has been previously described in primary care settings [29, 30], and could be added to reporting requirements for transplant candidate registration. While such screening could provide accurate patient-level SES data, standardized collection of SDH in clinical settings entails its own challenges, including a lack of consensus on best measurements and data collection practices, lack of collaboration between health systems and social services organizations, and technological challenges to capturing and retaining these data [31].…”
Section: Discussionmentioning
confidence: 99%
“…Clinician barriers such as time constraints, having inadequate risk assessment training and a lack of knowledge of available community resources for addressing SDOH (Beck, Klein & Kahn, 2012), in addition to concern or discomfort discussing sensitive topics such as income or domestic violence with patients and families (Beaune et al, 2014; Beck et al, 2012) have been reported. Other barriers to screening include the belief that assessing SDOH is outside the purview of clinical medical care (DeJong et al, 2016), or that it is a task that is better handled by trained social work teams (Pai et al, 2016). Finally, clinicians may also have the perception that SDOH are not remediable and therefore, assessment serves no purpose (Klein et al, 2013).…”
Section: Clinical Problemmentioning
confidence: 99%
“…Several studies employed an embedded social history template into the electronic medical record, for easy in person assessment during a clinical encounter (Beck et al, 2012; Gottlieb et al, 2015). Two of the medical-legal partnership studies used telephone and in person interviews to assess SDOH domains (DeJong et al, 2016; Weintraub et al, 2010). In contrast Kenyon, Sandel, Silverstein Shakir and Zuckerman (2007) used a helpful IHELLP mnemonic, which stood for income, housing/utilities, education, legal status/immigration, literacy, and personal safety, to guide clinicians during clinical encounters.…”
Section: Critical Appraisalmentioning
confidence: 99%
“…These functions are often problematic for health care providers due to a lack of understanding of what resources are available and the complicated system of federal, state, and local aid and assistance. 8 The need for health care transition services…”
Section: Limited Medical Home Accessmentioning
confidence: 99%
“…CSHCN who have insufficient insurance coverage (underinsured) experience comparable unmet needs to those without any insurance in terms of financial burden and access to care. 3 DeJong et al 8 report these children utilize Medicaid and other federal and state-funded insurance as well as other programs that provide for the care of a disabled child. These government programs have been experiencing severe cutbacks and shortages in recent years which negatively impact CSHCN.…”
Section: Inadequate Health Insurancementioning
confidence: 99%